Answer:
Z = 8.8 Y = - 42
Step-by-step explanation:
Y = 2 - 5Z
Y = 5 - 47
2 - 5Z = 5 - 47
- 5Z = - 44
5Z = 44
Z = 8.8
Y = 2 - 5 (8.8)
Y = 2 - 44
Y = - 41
Y = 5 - 47
Y = - 42
Answer:
C
Step-by-step explanation:
5 is b because 3/6 is equivalent to 1/2
6 is a because 1/6 is less than half
1cm = 10mm
15.24cm x 10 = 152.4mm
Hope this helps!!!
Answer:
No solutions
Step-by-step explanation:
–2(3x – 1) = –6x – 1
First distribute the left side
-6x + 2 = -6x - 1
Add 1 to both sides
-6x + 3 = -6x
Add 6x to both sides
3 = 0
This equation is not true because 3 does NOT equal 0. Therefor, this equation has no solutions.